ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENINGKATAN PRODUKSI PADI DI KABUPATEN LANGKAT SUMATERA UTARA - Lubis, Junita (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2018)
One of the central production of paddy in Indonesia is Langkat.The demand for paddy is increasing from time to time, following the increase of population. The study is aimed to analyze the influence of inputs used such as site of land, labor, seed, and fertilizer for toward paddy production in Langkat. The results indicated that site of land, labor, seed and fertilizer have positive sign and significance at Î± = 5% to influence the production of paddy in the study area. The coefficient of elasticity was found to be 1.671(marginally elastic), this implies that the production of paddy in langkat, provide increasing in returns, therefore it is suggested thatdiversification efforts are indeed need to secure the food security, especially in paddy for Langkat.